Kajian Atmosfir Terkendali untuk Memperlambat Penurunan Mutu Buah Mangga Arumanis selama Penyimpanan - I Made Suphartha Utama; Yohanes Setiyo; Ida Ayu Rina Puja; Nyoman Semadi (Jurnal Hortikultura Indonesia, 2011)
Arumanis Mango (Mangifera indica L. cv Arumanis) which is one of Indonesia’s tropical fruits having a high potency to be developed as an export commodity. Limited volumes of the fruit have been exported using air cargo and attempts in using sea freights with reefer containers for long distance market had not given convincing result. Therefore, efforts in optimizing the use of a reefer container are essential. Investigations, were performed in order to decelerate the deterioration fruits which involved different combined concentrations of O2 and CO2 gases during storage of Arumanis mango at cold (12+1.5oC) and room (28+2oC) temperatures. Four different combined gases of O2 and CO2, namely 5% O2 and 5 % CO2; 5% O2 and 10% CO2; 10% O2 and 5% CO2; and 10% O2 and 10% CO2 were surged surrounding the fruits stored at the cold and room temperatures. Fruits without treatments with the combined gases were prepared as kontrols. The investigation indicated that the cold temperature of storage was still the best way to slowing down the deterioration of the fruit. There were no significant different effects on the rate of deterioration among the fruits treated with the different combined concentrations of O2 and CO2. The controlled atmospheres, however, were better for storing the fruits compared to those stored without controlled atmosphere.Key words: controlled atmosphere, Arumanis, mango